The sherds of conquistadors: a petrological study of ceramics from Graciosa Bay and Pamua, Solomon Islands. Issue 1 (22nd April 2013) - Kelloway, Sarah J.; Gibbs, Martin; Craven, Steven
Abstract We present evidence linking vessel forms with ceramic wares resulting from the petrological analysis of 33 sherds from two sixteenth century Spanish colonial sites in the Solomon Islands. Our results expand the range of fabric types previously published, and comparative literature analyses support earlier studies suggesting probable ceramic origins in the Americas and Spain.